English Study Program of Universitas Riau Students' Perceptions of Using ChatGPT in Improving Their Writing Skills - Syafana Rihadatul Aisy; Supriusman Supriusman; Erni Erni (Journal of Educational Sciences, 2026)
This study investigated first-year English Study Program students’ perceptions of using ChatGPT in improving their writing skills at Universitas Riau. Writing remains a challenging skill for many EFL students, particularly in generating ideas, organizing content, and using appropriate language. A quantitative descriptive design was employed involving 39 students from Class 2A who had prior experience using ChatGPT. Data were collected using a 30-item Likert-scale questionnaire covering five indicators: idea development, organization and structure, language use and vocabulary, confidence and motivation, and ethical awareness and critical thinking. The findings revealed overall positive perceptions, with the highest mean in ethical awareness and critical thinking (M = 4.51) and language use and vocabulary (M = 4.18). Students reported that ChatGPT helped generate ideas, enrich vocabulary, improve sentence structure, and increase writing confidence. The study concludes that ChatGPT can serve as a supportive tool for writing improvement while complementing students’ critical thinking and creativity.